Writing the border : avoiding restorative nostalgia by using social media discourses to create a Borderdrama - Albertyn, Maria Adriana; Albertyn, Marina (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.